Who Owns What? Legal Analysis of Unit Ownership in Solo Urbana Residence under Indonesian Land Law - Oktaviani, Nadya Ivi (Indonesian Journal of Agrarian Law, 2025)
The development of vertical housing in Indonesia is increasing rapidly along with the increasing needs of urban communities for practical and strategic places to live, one of which is through the construction of apartments. However, behind this phenomenon, there are important issues related to the ownership of apartment units in the perspective of Indonesian land law. This article discusses juridically the form of ownership of apartment units through the mechanism of Property Rights on Flat Units (HMSRS), with a case study of Solo Urbana Residence in Surakarta City. In addition, this article also reviews the legal requirements that must be met so that the ownership status of an apartment unit can be considered valid, as well as how legal protection is provided to unit owners in the event of a dispute, both in the administrative, civil and criminal realms. By using normative juridical method and qualitative approach to regulations and legal literature, this article aims to provide understanding to the public to be more vigilant and understand their legal rights in apartment transactions.